2019
DOI: 10.1186/s12903-019-0763-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the level of cortisol, capillary blood glucose, and blood pressure in response to anxiety of patients rehabilitated with complete dentures

Abstract: Background The aim was to analyze the levels of stress of edentulous patients through the state-trait anxiety inventory (STAI) and salivary flow through the visual analogue scale (VAS) xerostomia questionnaire, as well as analyze the levels of cortisol, capillary blood glucose, and blood pressure (BP) before and after the installation of complete dentures. Methods Fifty patients were evaluated. The STAI and VAS xerostomia questionnaire were applied before the installati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Similarly, Kuchler et al evaluated the analgesic needs as well as the stress response in spine surgery based on the RBS and cortisol levels between postoperative epidurally administered levobupivacaine and administered saline placebo, the RBS did not have any significant different values despite the VAS score and the analgesic requirements mean values were statistically significant lower with the intervention group than the control group at the measured time intervals [20].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kuchler et al evaluated the analgesic needs as well as the stress response in spine surgery based on the RBS and cortisol levels between postoperative epidurally administered levobupivacaine and administered saline placebo, the RBS did not have any significant different values despite the VAS score and the analgesic requirements mean values were statistically significant lower with the intervention group than the control group at the measured time intervals [20].…”
Section: Discussionmentioning
confidence: 99%
“…In the process of tracheal intubation and tracheal extubation, the strong stimulation of the tracheal tube to the sidewall and glottis of the trachea can re exly excite the sympathetic nerves, resulting in increased secretion of catecholamines in the body, the blood pressure and heart rate got increased, which seriously affects the patients' health life safety [17,18] . The stress reaction also promotes the catabolism of sugar, protein and fat, causing continuous increase in blood sugar during and after surgery, leading to di culty in wound healing and prone to infection [19,20] . The results of this study showed that the adrenaline, cortisol, and blood sugar levels of the test group at 12h and 48h after surgery were signi cantly lower than those of the control group, indicating that systematic analepsia management strategy can effectively reduce the patients' stress reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The second is by increasing glycogenolysis in the liver, thereby releasing large amounts of glucose into the bloodstream within minutes. Excess of gluconeogenesis and glycogenolysis causes hyperglycemia so that the blood becomes more viscous and then aggravate the work of the heart (18).…”
Section: Discussionmentioning
confidence: 99%